Marching for justice. - Eastern Women's Federation of Sri Lanka
A long march and a memorandum draw public attention to the fact that the lives and livelihoods of fisherwomen affected by thew tsunami and the ongoing war in Sri Lanka's eastern coast, continue to hang in the balance.